The Effect of Third Party Funds and Non-Performing Financing on the Performance of Islamic Banks (Case Study at PT Bank Muamalat Indonesia Tbk) - Alamsyah, Malikul Hafiz (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
PT Bank Muamalat Indonesia Tbk. (“Bank Muamalat Indonesia”) is a financial institution that functions as a collector of funds from the public in the form of deposits and distributes them back to the public in the form of financing based on sharia principles. Sources of funds originating from public third party funds are in the form of Wadi'ah Current Accounts, Wadi’ah and Mudharabah Savings and Mudharabah Deposits. As a financial institution, the management of third party funds and redistribution in the form of financing will determine the bank's operating income, which in turn will affect the bank's financial performance which in this study is seen from profitability as measured by the Return on Assets ("ROA") ratio. The purpose of this study is to find out the influence of Third Party Funds ("TPF") and Non-Performing Financing ("NPF") on the financial performance of Bank Muamalat Indonesia. The type of research used is quantitative research, which is a type of research based on data analysis that can be calculated or is in the form of numbers. Data were collected through literature studies and 7-year financial reports of Bank Muamalat Indonesia, starting from 2014 to 2020. The results showed that 35.3% of the financial performance of Bank Muamalat was influenced simultaneously by TPF and NPF. Another variable of 64.7% that affects financial performance is not included in this study.